Application of functional coatings in water electrolyzers and fuel cells - Zhou, Jiaxin; Ming, Fangwang; Liang, Hanfeng (Nanoscale, 2025)
Hydrogen, a sustainable energy carrier, plays a pivotal role in decarbonizing various industrial sectors. Key devices such as water electrolyzers and fuel cells enable a sustainable hydrogen cycle by producing hydrogen using renewable energies and converting hydrogen into electricity. The efficiency of these devices is primarily determined by electrocatalysts and other critical components like membranes, gas diffusion layers and bipolar plates. The dynamic and complex triple-phase reactions as well as the corrosive operational environments in these devices present significant challenges in achieving optimal performance and durability. This review not only summarizes recent advances in functional coatings but also elucidates the underlying mechanisms by which coatings modulate interfacial interactions and mitigate degradation. We further propose a roadmap for designing next-generation multifunctional coatings, emphasizing their potential to bridge the gap between laboratory research and industrial applications. This review summarizes recent advances in functional coatings in water electrolyzers and fuel cells, covering both compositional design and mechanism understanding of coating materials.